The mammalian 43-kD acetylcholine receptor-associated protein (RAPsyn) is expressed in some nonmuscle cells (The Rockefeller University Press, 1989)
Torpedo electric organ and vertebrate neuromuscular junctions contain the receptor-associated protein of the synapse (RAPsyn) (previously referred to as the 43K protein), a nonactin, 43,000-Mr peripheral membrane protein associated with the cytoplasmic face of postsynaptic membranes at areas of high nicotinic acetylcholine receptor (AChR) density. Although not directly demonstrated, several lines of evidence suggest that RAPsyn is involved in the synthesis and/or maintenance of such AChR clusters. Microscopic and biochemical studies had previously indicated that RAPsyn expression is restricted to differentiated, AChR- synthesizing cells. Our recent finding that RAPsyn is also produced in undifferentiated myocytes (Frail, D.E., L.S. Musil, a. Bonanno, and J.P. Merlie, 1989. Neuron. 2:1077-1086) led to to examine whether RAPsyn is synthesized in cell types that never express AChR (i.e., cells of other than skeletal muscle origin). Various primary and established rodent cell lines were metabolically labeled with [35S]methionine, and extracts were immunoprecipitated with a monospecific anti-RAPsyn serum. Analysis of these immunoprecipitates by SDS-PAGE revealed detectable RAPsyn synthesis in some (notably fibroblast and Leydig tumor cell lines and primary cardiac cells) but not all (hepatocyte- and lymphocyte-derived) cell types. These results were further substantiated by peptide mapping studies of RAPsyn immunoprecipitated from different cells and quantitation of RAPsyn- encoding mRNA levels in mouse tissues. RAPsyn synthesized in both muscle and nonmuscle cells was shown to be tightly associated with membranes. These findings demonstrate that RAPsyn is not specific to skeletal muscle-derived cells and imply that it may function in a capacity either in addition to or instead of AChR clustering.